A mathematical poetry book from Nepal. Issue 3 (1st September 2020) - Basyal, Deepak
Abstract : The Rana regime (1846–1951) in Nepal is widely known for its lack of support for public education and its notorious opposition to women's rights. Near the end of that regime, a mathematical textbook composed in the form of poetic verses was published in the Nepali language, purportedly written by a female author. This article explores the provenance, presentation style, authorship mystery, and unique mathematical content of this book. Furthermore, we explore how mathematical problems may reveal socio-cultural aspects of a country, and how original historical sources such as the one examined in this paper can be useful in the teaching and learning of mathematics today.